Some Sociological reflections on development in the Eastern Himalayas - Nepali, Gopal Singh (Occasional Papers in Sociology and Anthropology, 2008)
DOI: 10.3126/opsa.v2i0.1066 Occasional Papers in Sociology and Anthropology Vol.2 1990 p.24-31